(untitled) (Research, Society and Development, 2023)
To analyze the experience of puerperal women in relation to vaginal delivery. Descriptive qualitative research. Data collection took place through a semi-structured interview with puerperal women assisted in the Family Health Strategies (ESF) of a medium-sized municipality in the interior of Rio Grande do Sul/RS. Data analysis was performed through content analysis. With regard to the delivery experience, most pregnant women mentioned it as a quick process, but uncomfortable and accompanied by pain. The main feelings revolved around joy and anxiety, and most of these felt the lack of a companion during the parturition process. With regard to the guidance received by the mothers about the time of delivery, it was observed that the nursing team provided insufficient and incomplete information. However, all of them were satisfied and supported by the nursing care, demonstrating all the affection, attention and respect they had with them. It was possible to understand the main experiences and feelings experienced by the puerperal women about childbirth, as well as to identify the weaknesses and negative points to be improved during care, not only by nursing, but jointly by the entire multidisciplinary team.